A comprehensive review on the processing, composition, and safety of fermented rice products and advanced methods for improving its quality - Fitri, Nursyah; Chan, Sharon Xi Ying; Qadi, Wasim S.M.; Wong, Pei Lou; Hellal, Khaoula; Hamezah, Hamizah Shahirah; Mediani, Ahmed; Abas, Faridah (Academic Press Inc., 2025)
In many countries, rice, which contains numerous nutrients, is a primary staple food consumed by more than half of the world's population. Fermenting rice efficiently enhances its nutrient bioavailability and promotes better health benefits. Many cultures favor fermented rice for both its health advantages and its appealing sensory qualities. It is rich in microflora and functions as a probiotic, thus improving immunity and digestive health. This review includes information from all accessible library databases (i.e., Google Scholar, Web of Science, Scopus, ScienceDirect, and PubMed Central), including books and online databases from 1994 to 2024. Various aspects related to fermented rice including the fermentation process, microbial and sensory properties, physicochemical and biochemical changes in fermented rice products, safety risks, concern about fermented rice products, halal issues, safety regulations, quantitative risk assessment, Hazard Analysis Critical Control Point (HACCP) system, basic good manufacturing and hygiene practices, and metabolomics aspects are discussed. Additionally, this review can benefit the researchers as well as food sectors involved in the commercialization of fermented rice by providing fundamental insights into fermentation processes and guidance for generating high-quality products without compromising customer safety and health.